2023
DOI: 10.3390/biology12040490
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, Nutritional and Transcriptomic Responses of Sturgeon (Acipenser schrenckii) to Complete Substitution of Fishmeal with Cottonseed Protein Concentrate in Aquafeed

Abstract: This study estimated the effect of substituting fishmeal completely with cottonseed protein concentrate (CPC) in the diet of sturgeon (Acipenser schrenckii) on growth, digestive physiology, and hepatic gene expression. A control diet containing fishmeal and an experimental diet based on CPC was designed. The study was conducted for 56 days in indoor recirculating aquaculture systems. The results showed that weight gain, feed efficiency, and whole-body essential amino acids (EAAs) all decreased significantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
1
2
0
Order By: Relevance
“…The results indicated that a higher substitution of FM with CPC influences the hepatic function in hybrid culter. Similar observations have been reported in hybrid grouper [21], Amur sturgeon (Acipenser schrenckii) [34], and rainbow trout [35]. Serum TP and ALB levels serve as indicators for protein metabolic status and immune capacity in fish [36].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The results indicated that a higher substitution of FM with CPC influences the hepatic function in hybrid culter. Similar observations have been reported in hybrid grouper [21], Amur sturgeon (Acipenser schrenckii) [34], and rainbow trout [35]. Serum TP and ALB levels serve as indicators for protein metabolic status and immune capacity in fish [36].…”
Section: Discussionsupporting
confidence: 80%
“…Our findings are consistent with previous research on Nile tilapia (Oreochromis niloticus) [42] and large yellow croaker (Larimichthys crocea) [43], which reported that increasing CPC in the diet did not significantly affect EAA or TAA contents in muscles. However, studies on largemouth bass [10] and Amur sturgeon [34] have shown that replacing FM with a high proportion of CPC significantly reduced muscular TAA and EAA contents. This may be explained by higher dietary CPC content causing an increase in gossypol level or an imbalance in amino acid compositions.…”
Section: Discussionmentioning
confidence: 96%
“…For example, cottonseed meal, a byproduct of oilseed crops and fibers (55-68% protein content) [11], is the common protein source for poultry feed [12]. In recent years, it has received attention as an alternative protein to FM in aquafeeds, such as rainbow trout (Oncorhynchus mykiss) [13], large yellow croaker (Larimichthys crocea) [14], sturgeon (Acipenser schrenckii) [15], etc., but due to the toxic effects of free cottonseed on fish, the high percentage of addition may affect the growth and health of fish. According to statistics, in 2020, the global meat production was approximately 252.6 billion kg, including 57.7 billion kg of beef, 99.1 billion kg of chicken, and 95.8 billion kg of pork [16], while the meat industry produces several byproducts during slaughter and processing, such as blood, bones, skin, organs, internal organs, horns, hooves, feet, and skulls [17].…”
Section: Introductionmentioning
confidence: 99%